Variation in fibrinogen FGG and FGA genes and risk of stroke - Cheung, Elim Y. L.; Bos, Michiel J.; Leebeek, Frank W. G.; Koudstaal, Peter J.; Hofman, Albert; de Maat, Moniek P. M.; Breteler, Monique M. B. (Thrombosis and Haemostasis, 2008)
Haplotypes of the fibrinogen gamma and alpha (FGG and FGA) genes are associated with the structure of the fibrin network and may therefore influence the risk of stroke. We investigated the relationship between common variation in these genes with ischemic and haemorrhagic stroke. The study was based on 6,275 participants of the prospective population-based Rotterdam Study who at baseline (1990 – 1993) were aged 55 years or over, free from stroke, and had successful assessment of at least one FGG or FGA single nucleotide polymorphisms (SNP). Common haplotypes were estimated using seven tagging SNPs across a 30 kb region containing the FGG and FGA genes. Follow-up for incident stroke was complete until January 1,2005. Associations between constructed haplotypes and risk of stroke were estimated with an age- and sex-adjusted logistic regression model. We observed 668 strokes, of which 393 were ischemic and 62 haemorrhagic, during a median follow-up time of 10.1 years. FGG+FGA haplotype 3 (H3) was associated with an increased risk of ischemic stroke (odds ratio [OR] 1.36, 95% confidence interval [CI] 1.09–1.69) and the risk estimate for hemorrhagic stroke was 0.71 (95% CI 0.46–1.09) compared to the most frequent H1. The FGG and FGA genes were not associated with stroke or its subtypes when analyzed separately. In conclusion, risk of ischemic stroke was higher in FGG+FGA H3 than in H1. The results suggested that an opposite association may exist for haemorrhagic stroke.
Keywords: Stroke; fibrinogen; haplotype